Identification of Conserved and Divergent Strigolactone Receptors in Sugarcane Reveals a Key Residue Crucial for Plant Branching Control - Hu, Anqi; Zhao, Qiaoqiao; Chen, Li; Zhao, Jinping; Wang, Yuehua; Feng, Kuiliang; Wu, Ling; Xie, Miao; Zhou, Xuemei; Xiao, Langtao; Ming, Zhenhua; Zhang, Meng; et al. (Frontiers in Plant Science, 2021)
Strigolactones (SLs) are a class of important plant hormones mainly regulating plant architecture such as branching, which is crucial for crop yield. It is valuable to study SL signaling pathway and its physiological function in sugarcane, the most important sugar crop, for further molecular breeding. Here, two putative SL receptors SsD14a/b and the interacting F-box protein SsMAX2 were identified in Saccharum spontaneum. SL induced both SsD14a and SsD14b to interact with SsMAX2 in yeast. SsD14a, but not SsD14b, could bind with AtMAX2 and AtSMXL7/SsSMXL7. Overexpression of SsD14a or SsMAX2 rescued the increased branching phenotypes of Arabidopsis thaliana d14-1 or max2-3 mutants, respectively. Moreover, the crystal structure of N-terminal truncated SsD14a was solved, with an overall structure identical to AtD14 and OsD14 in the open state, consistent with its conserved branching suppression capacity in Arabidopsis. In line with the biochemical observations, SsD14b could not completely complement in d14-1 although these two SsD14 proteins have almost identical primary sequences except for very few residues. Complement with the combination of SsD14b and SsMAX2 still failed to rescue the d14-1 max2-3 double mutant multi-branching phenotype, indicating SsD14b–AtSMXL7 complex formation is required for regulating branching. Mutagenesis analyses revealed that residue R310 at α10 helix of SsD14a was crucial for the binding with SsSMXL7/AtSMXL7 but not SsMAX2. The site-equivalent single-residue P304R substitution enabled SsD14b to bind with AtMAX2 and AtSMXL7/SsSMXL7 and to rescue the phenotype of d14-1 max2-3 together with SsMAX2. Moreover, this conserved Arg residue across species including rice and Arabidopsis determined the activity of SL receptors through maintaining their interaction with SMXL repressors. Taken together, our work identified conserved and divergent strigolactone receptors in sugarcane core SL signaling pathway and revealed a key residue crucial for plant branching control.